INTERAKSIONISME SIMBOLIK PADA TRADISI SAJEN AMONG DI MALANG - Pratiwi, Ananda; Saffanah, Winin Maulidya; Nisa, Azizah Khoirun; Zakiyah, Nuris (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
The Sajen Among tradition in the villages of Sekarpuro, Asrikaton, and Tanggung in Malang Regency is a Javanese cultural ritual rich in symbolic and spiritual meaning. This study examines its existence, its symbols, and its significance through a qualitative approach. Based on in-depth interviews with six informants across the three villages, the research reveals distinct definitions and purposes of Sajen Among in each community: in Sekarpuro, it serves as an offering to ancestral spirits; in Asrikaton, as protection for spiritual kin; and in Tanggung, as an expression of gratitude. The ritual elements such as coffee, water, rice, traditional snacks, betel leaves, tobacco, cigarettes, incense, areca nuts, whiting, and uncaria, each embody unique Javanese cultural values. Viewed through the lens of symbolic interactionism, the meaning of these offerings is constructed through social interactions, including grave pilgrimages and strict adherence to ritual protocols. Despite challenges to its preservation, such as stigmatization as “musyrik” and pressures of modernization, Sajen Among continues to endure as a vital expression of cultural and spiritual identity